SISTEM INFORMASI MANAJEMEN PENGELOLAAN KEUANGAN PADA YAYASAN AL-HASNA KLATEN MENGGUNAKAN METODE RAPID APPLICATION DEVELOPMENT (RAD) - Istri Sulistyowati; Yusuf, Mahmud; Marjukah, Anis (Journal of Computer Science and Technology (JCS-TECH), 2024)
This research aims to create a financial management information system for the Al-Hasna Foundation which operates in the world of education. This foundation oversees basic level educational institutions and informal education. The formal educational institutions are kindergartens and elementary schools, while the informal educational institutions are play groups and Al-Qur'an educational park. The system created is used to manage all existing educational institutions into one. The system development method used is the Rapid Application Development (RAD) method. For database design using normalization and Entity Relationship Diagram (ERD). The first design step is conceptual design using a Context Diagram. The second step is logical design, namely design that aims to prepare the necessary and best data structures to be implemented. The final step is physical design, namely implementing the logic model into the Microsoft Visual Foxpro 9 programming language so that the desired system is obtained. The result of this research is an information system for processing financial data for the Al-Hasna Foundation which manages all student payment data. The results of this system are student payment reports, both overall recapitulation and each payment item. This system also produces reports about student data. Keywords: School Finanial Information System, Al-Hasna Fondation